Induced Lactation and Its Effects on Mahram Relationships from The Perspective of Jurisprudence Scholars - Angreani, Santi; arma, hariri ocviani (Jurnal AL-AHKAM, 2024)
The latest studies in the field of health, especially in the field of breastfeeding, which provides opportunities for women to breastfeed babies without going through the process of pregnancy and childbirth. This research uses the type of library research (Library Research). The book of fiqh scholars as a primary source, while for secondary sources, the author uses the opinions of contemporary scholars, books, journals, and other supporting books. The results of the analysis obtained that the law of using the method of induction of lactation in a barren woman or girl is ibahah as long as there is no harm to the breastfeeder and the suckling. Some scholars say that there is a mahram relationship between the mother of the milk and her brothers and sisters, while some scholars say that there is no effect of induced lactation on the mahram relationship. The author's opinion on this khilafiah issue is more inclined towards the opinion of the scholars who say that there is a mahram relationship between the two of them and their brothers and sisters because the source of the milk is from the same woman, while the husband of the mother of the milk does not result in a mahram relationship because the milk comes out not because of wata' with her husband and the child is not part of her husband.